Application of Mechanical Waves in Rock Media for Earthquake Disaster Risk Analysis as an Enrichment of Physics Practicum - Arif Ismul Hadi; Budi Harlianto; Elfi Yuliza; Hana Raihana; Andre Rahmat Al Ansory (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
The phenomenon of mechanical waves propagation in rock media is difficult to detect without the use of tools. To "see" the propagation of seismic waves, tools can be used in the form of a main unit monitor on a set of digital Seismograph-16S24-P 24 geophone channel tools. The community service activity aims to provide an understanding of the basic concepts of mechanical wave propagation in rocks to senior high school students throughout Bengkulu City as an enrichment for Physics Practicum. The method used to achieve the objectives of this community service activity is carried out through the stages of Focus Group Discussion (FGD), field data acquisition, data processing, data analysis and interpretation. Activity evaluation is carried out by observing activity participants in data acquisition, data processing, data analysis and interpretation. The results of the activity show that the activity participants have a good understanding of the basic concept of mechanical wave propagation in rocks. Furthermore, Bengkulu City Physics Teachers can transmit this knowledge to senior high school students as an enrichment for Physics Practicum. The material on the application of mechanical waves to rock media can also be used as a learning tool based on disaster risk reduction in the main physics subject, according to the characteristics of the study area.